Auditoría financiera y su Incidencia en la rentabilidad de la empresa Plasticentro, Cantón La Maná, Año 2012. - Guarochico Ortega, Aida Yolanda (2015)
This research aims to determine the incidence of financial audit in profitability Plasticentro, canton La Manà, year 2012.para as to evaluate the level of trust in financial information, in addition to examining the involvement of planning resources and analyze the performance of the legal basis of the financial area the audit process was carried out through the following phases considering the preconditions for the development of the same activities, the first phase is the preliminary knowledge, the second phase consists of file planning, the third stage is the execution and analysis of financial statements and finally the fourth phase in which are the communication of results, for the proper analysis of the results IFRS for SMEs which allowed us to endorse the accuracy of the applied information to obtain an acceptable degree of confidence in applying equally to accounts analysis was performed to determine whether there were flaws in the process however after applying the same it was found that the accounts are reasonably counted and the results of its operations for the year ended on that date are consistent with generally accepted accounting principles.